2018
DOI: 10.1109/lsp.2017.2721966
|View full text |Cite
|
Sign up to set email alerts
|

Ramanujan Sums as Derivatives and Applications

Abstract: In 1918 S. Ramanujan defined a family of trigonometric sum now known as Ramanujan sums. In the last few years, Ramanujan sums have inspired the signal processing community. In this paper, we have defined an operator termed here as Ramanujan operator. In this paper it has been proved that these operator possesses properties of first derivative and second derivative with a particular shift. Generalised multiplicative property and new method of computing Ramanujan sums are also derived in terms of interpolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…By construction each column of R N are pairwise orthogonal.Hence R N is invertible and β N = R −1 N x N . In an earlier work authors have shown that Ramanujan sequences are basically first order derivative [1]. Hence β 1 is smoothing coefficient and β N (N > 1) can be interpreted as finer details of a signal.…”
Section: Examplementioning
confidence: 99%
See 3 more Smart Citations
“…By construction each column of R N are pairwise orthogonal.Hence R N is invertible and β N = R −1 N x N . In an earlier work authors have shown that Ramanujan sequences are basically first order derivative [1]. Hence β 1 is smoothing coefficient and β N (N > 1) can be interpreted as finer details of a signal.…”
Section: Examplementioning
confidence: 99%
“…The great Indian mathematician S.Ramanujan defined a trigonometric sum [9] as c q (n) = q k=1 (k,q)=1 exp j2πkn q (1) where (k, q) = 1 implies that k and q are relatively prime. Various standard arithmetic functions like Mobius function µ(n), Euler's toient function φ(n),von Mangoldt function , Riemann-zeta function ζ(s) were represented using these Ramanujan sums.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ramanujan sums have been considered for application in Signal Processing, e.g. in [11] and [22]. In particular, they have been used to study the periodicity structure of streaming data [10], and also how the periodicity of a sampled continuous signal does not imply the periodicity of the continuous signal [9].…”
Section: Introductionmentioning
confidence: 99%